2012
DOI: 10.1002/mnfr.201200237
|View full text |Cite
|
Sign up to set email alerts
|

Grape seed proanthocyanidins repress the hepatic lipid regulators miR‐33 and miR‐122 in rats

Abstract: These results suggest that proanthocyanidin treatment increased hepatic cholesterol efflux to produce new HDL particles by repressing miR-33, and it reduced lipogenesis by repressing miR-122. These results highlight a new mechanism by which grape seed proanthocyanidins produce hypolipidemia through their effects on miRNA modulators of lipid metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 47 publications
1
72
0
Order By: Relevance
“…And the dosages of proanthocyanidins used in animal models ranged from 10-250 mg/kg body weight. It was reported that a concentration of 25 μg/ml of proanthocyanidins is need in vitro to reach the significant regulation of miRNA [56]. Results from Qiu et alindicated that after a single oral administration of 100 mg/kg body weight for each compound, the plasma concentrations of EGC and EGCG dimer were 7.5 and 9.3 nmol/L, separately [57].…”
Section: Accepted Manuscriptmentioning
confidence: 93%
See 1 more Smart Citation
“…And the dosages of proanthocyanidins used in animal models ranged from 10-250 mg/kg body weight. It was reported that a concentration of 25 μg/ml of proanthocyanidins is need in vitro to reach the significant regulation of miRNA [56]. Results from Qiu et alindicated that after a single oral administration of 100 mg/kg body weight for each compound, the plasma concentrations of EGC and EGCG dimer were 7.5 and 9.3 nmol/L, separately [57].…”
Section: Accepted Manuscriptmentioning
confidence: 93%
“…Results from Qiu et alindicated that after a single oral administration of 100 mg/kg body weight for each compound, the plasma concentrations of EGC and EGCG dimer were 7.5 and 9.3 nmol/L, separately [57]. and their metabolites (about 17.18 μmol/L in total) were five times higher than that in the cell media at 25 μg/ml of proanthocyanidins [56]. Therefore, the concentrations (20-60 μg/ml) we used in the present study were enough to modulate miRNA levels in vivo.…”
Section: Accepted Manuscriptmentioning
confidence: 95%
“…The doses of NaF and GSPE were selected based on previous studies conducted in our laboratory [14,15].…”
Section: Chemicalsmentioning
confidence: 99%
“…Recently, it was reported that miR-122 and miR-33a/b played a major role in regulating fatty acids and cholesterol metabolism (Baselga-Escudero et al, 2012;Esau et al, 2006;Rayner et al, 2011). miR-122 is a highly liver-specific miRNA, making up 70% of the total miRNA population in liver (Wen & Friedman, 2012).…”
Section: Introductionmentioning
confidence: 99%